The Concept Of Vowel Sounds To Students Ability In Phonology - Sonia Sabilla; Masriyanti Nasution; Yani Lubis (Pusat Riset dan Inovasi Nasional, 2023)
This articlei is motivateid by thei importancei of voweil souinds to suipport thei ability to reiad and writei in Einglish. Voweil souinds ability is an ability that is oftein oveirlookeid whein compareid to speiak and conveirsation compreiheinsion, althouigh theirei is a lot of liteiratuirei which stateis that reiseiarcheirs and eiduicators agreiei that souinds skills arei important to bei tauight. Uintil now, theirei arei still many stuideints in geineiral who do not uindeirstand voweil souinds . Theireiforei, this articlei discuisseis speilling and speilling variants. Writing this articlei aims: 1) to know thei conceipt of voweil souinds 2) to find ouit voweil souinds 3) To find ouit thei correict voweil souinds misconceiptions. Thei meithod uiseid is a meithod by seiarching baseid on eixisting liteiratuirei and articleis. Thei data colleiction teichniquiei is baseid on liteiratuirei and articleis reilateid to voweil souinds. Thei reisuilt of this articlei is that speilling has a veiry big fuinction in writing, thei first impreission that thei reiadeir geits is thei voweil of souinds from an articlei beiforei hei uindeirstands thei meissagei thei auithor wants to conveiy. An articlei with a varieity of words which is muich morei inteireisting to reiad than an articlei that uiseis thei samei words oveir and oveir again. Many stuideints feieil that souinds with thei correict voweil souinds is veiry difficuilt to do.